DANCE AS A SOCIAL GIFT: A STUDY OF MARCEL MAUSS'S THEORY OF THE GIFT IN PERFORMING ARTS PRACTICE: DANCE AS A SOCIAL GIFT: A STUDY OF MARCEL MAUSS'S THEORY OF THE GIFT IN PERFORMING ARTS PRACTICE - Aidah, Hasna; Nursilah, Nursilah (International Journal of Performing Arts (IJPA), 2024)
This article discusses the relevance of Marcel Mauss's The Gift theory in understanding dance as aform of symbolic exchange in the context of performing arts. Based on a conceptual study and aperformance anthropology approach, this paper highlights the main principle in Mauss's theory,namely the obligation to give, receive, and reciprocate, which can be interpreted as a social structurethat binds the relationship between dancers, audiences, and society. In dance practice, the act ofdancing is seen as a "social gift" that contains moral, spiritual, and cultural values. The dancer'smovements, expressions, and performativity function not only as aesthetic representations, but alsoas a means of communication and exchange of meaning that creates a reciprocal relationshipbetween the performer and the recipient of the performance. Through an analysis of the socialfunction of dance, this article shows that the performance process is a total social event ( total socialfact ), as explained by Mauss, where the values of solidarity, empathy, and appreciation are realizedthrough symbolic interaction. The concept of the "soul of the gift" ( hau ) in Mauss's theory isreinterpreted as the artistic spirit in the performance that fosters emotional resonance betweendancers and audiences. Thus, The Gift theory not only enriches understanding of the social functionof performing arts, but also offers a new conceptual framework for dance education and practice inthe modern era.